Specific steps in the operation determine resident speed: Experience with a live tissue simulation model of laparoscopic nephrectomy - Eber, Jackson; Peterson, Andrew C. (Frontiers in Surgery, 2022)
Introduction It is increasingly important to identify and eliminate inefficiencies in resident education. We hypothesize that slower performance of specific operative steps in laparoscopic nephrectomy accounts for much of the slower operative speed observed in junior residents vs. their senior colleagues. Therefore, we sought to evaluate the by-step time-differential between experienced senior residents and their junior colleagues in a live-tissue simulation. Materials and methods Residents participated in our swine model surgical simulation of laparoscopic radical and partial nephrectomy (LRNx and LPNx). PGY5 and 6 residents were considered senior; junior residents were PGY3 and 4. We defined discrete surgical steps. Residents' post-graduate training levels were tracked and time-to-completion of each operative step was recorded. Results Seven live-tissue simulations sessions took place, with 12 residents conducting 22 operations (12 LRNx, 10 LPNx). On average, each resident operated in 2 simulation sessions (range 1–4). The average time required by senior residents for LPNx was 152 min; junior residents required 173 min (p = 0.35). When considering the operative steps, juniors required nearly twice as much time to achieve hilar control (42 min vs. 23 min, p = 0.03). Significant differences in performance time were not seen in the other steps. Discussion The performance differential between senior and junior residents conducting nephrectomies was most evident during hilar dissection. Our study suggests that specific efforts should be focused on teaching junior residents the skills required for this step early in their training.